TAMBAR 'KUNING' SEBAGAI REPRESENTASI EKOLOGIS DALAM BUDAYA BATAK KARO: KAJIAN EKOLINGUISTIK - Br Karo Sekali, Emmya Kristina; Herlina, Herlina; Sinulingga, Jekmen; Damanik, Ramlan; Tampubolon, Flansius (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to examine tambar kuning, a traditional medicine in the Batak Karo community, as an ecological representation through an ecolinguistic approach. Tambar kuning consists of two main types: kuning melas (hot balm) and kuning mbergeh (cold balm), each used according to bodily conditions and environmental factors. The research was conducted in Gurusinga Village, Karo Regency, using a descriptive qualitative method. Data were obtained through observation, interviews, and literature study. The findings show that tambar kuning not only functions as a healing agent but also reflects the Karo people's local knowledge in utilizing natural resources. Its composition is based on local flora, selected for their warming or cooling effects. This practice demonstrates a strong interrelation between language, culture, and ecology. Furthermore, the lexical items related to tambar kuning serve as verbal representations of the community's ecological knowledge system. The study concludes that tambar kuning is an intangible cultural heritage containing ecological and linguistic values that should be preserved as part of the collective identity of the Karo people.